Clinicopathological features of choledocholithiasis patients with high aminotransferase levels without cholangitis: Prospective comparative study. Issue 42 (October 2016) - Huh, Cheal Wung; Jang, Sung Ill; Lim, Beom Jin; Kim, Hee Wook; Kim, Jae Keun; Park, Jun Sung; Kim, Ja Kyung; Lee, Se Joon; Lee, Dong Ki
Abstract : Abstract: Common bile duct (CBD) stones are generally associated with greater elevations of alkaline phosphatase and gamma-glutamyl transpeptidase levels than aspartate aminotransferase and alanine aminotransferase levels. However, some patients with CBD stones show markedly increased aminotransferase levels, sometimes leading to the misdiagnosis of liver disease. Therefore, the aim of this study was to investigate the clinicopathologic features of patients with CBD stones and high aminotransferase levels. This prospective cohort study included 882 patients diagnosed with CBD stones using endoscopic retrograde cholangiopancreatography (ERCP). Among these patients, 38 (4.3%) exhibited aminotransferase levels above 400 IU/L without cholangitis (gallstone hepatitis [GSH] group), and 116 (13.2%) exhibited normal aminotransferase levels (control group). We compared groups in terms of clinical features, laboratory test results, radiologic images, and ERCP findings such as CBD diameter, CBD stone diameter and number, and periampullary diverticulum. Liver biopsy was performed for patients in the GSH group. GSH patients were younger and more likely to have gallbladder stones than control patients, implying a higher incidence of gallbladder stone migration. Also, GSH patients experienced more severe, short-lasting abdominal pain. ERCP showed narrower CBDs in GSH patients than in control patients. Histological analysis of liver tissue from GSH patients showed no abnormalities except for mild inflammation. Compared with control patients, GSH patients were younger and showed more severe, short-lasting abdominal pain, which could be due to a sudden increase of CBD pressure resulting from the migration of gallstones through narrower CBDs. These clinical features could be helpful not only for the differential diagnosis of liver disease but also for investigating the underlying mechanisms of liver damage in obstructive jaundice. Moreover, we propose a new definition of "gallstone hepatitis" based on the specific clinicopathologic characteristics observed in our patients.